Adaptability to High Temperature and Stay-Green Genotypes Associated With Variations in Antioxidant, Chlorophyll Metabolism, and γ-Aminobutyric Acid Accumulation in Creeping Bentgrass Species - Li, Zhou; Tang, Mingyan; Hassan, Muhammad Jawad; Zhang, Yan; Han, Liebao; Peng, Yan (Frontiers in Plant Science, 2021)
High temperature weather limits cultivation and utilization of cool-season plants in many regions worldwide. Recently, extreme hot waves sweep across the globe in summer leading to enormous economic loss. Evaluation and identification of genotypic variation in thermotolerance within the species is critical to breeding for environmental adaptation and also provide potential materials to explore thermo-resistant mechanism in plants. Forty-two accessions of creeping bentgrass (Agrostis stolonifera) which is a cool-season perennial grass for turf and ecological remediation were collected from fifteen different countries. Physiological traits including chlorophyll (Chl) content, electrolyte leakage, photochemical efficiency, performance index on absorption basis, leaf relative water content, and osmotic potential were used for evaluating heat tolerance of these materials in controlled growth chambers and field in summer. Stay-green and early-ageing genotypes were selected to further reveal potential mechanism of tolerance to senescence and heat damage associated with alterations in Chl metabolism, antioxidant and photosynthetic capacity, and endogenous γ-aminobutyric acid (GABA). Findings showed that there were significant genetic variations in physiological traits among 42 materials in response to high temperature stress. The 13M, the PROVIDENCE, and the LOFTS L-93 were the top three accessions with better tolerance to heat and summer stress than other materials based on laboratory and field tests. In response to heat stress, stay-green genotype PROVIDENCE exhibited significantly higher photochemical efficiency, net photosynthetic rate, transpiration rate, and water use efficiency than the heat-susceptible W6 6570. Delayed leaf senescence in relation to less Chl loss was detected in the PROVIDENCE associated with maintenance of significantly higher expression levels of Chl-anabolic genes (AsCHLH, AsPBGD, and AsPOR) and lower Chl-catabolic gene AsPPH under heat stress. Genetic attributes including better scavenging capacity of reactive oxygen species and higher endogenous γ-aminobutyric acid content could play positive roles in alleviating heat-induced senescence, oxidative damage, and metabolic disturbance in the PROVIDENCE.